2012
DOI: 10.1111/j.1540-8175.2012.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Right Ventricular Regional Volume and Systolic Function in Patients with Pulmonary Arterial Hypertension Using Three‐Dimensional Echocardiography

Abstract: In patients with PAH, RV regional volume was enlarged and systolic function was impaired with distinct characteristics; regional EF in the inflow compartment and global EF were inversely correlated with PASP and PVR. Evaluation of RV regional systolic function using RT3DE may play a potential role in the noninvasive assessment of the severity of PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
(81 reference statements)
2
23
0
Order By: Relevance
“…The decrement in RV EF in operated animals and patients with pressure overload has been reported in previous studies . Negative relationship between RV systolic function and RV after load was demonstrated in patients with pulmonary hypertension . Our findings were compatible with a previously tissue Doppler study which reported the relationship between pulmonary vascular bed and RV function in patients with ASD .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrement in RV EF in operated animals and patients with pressure overload has been reported in previous studies . Negative relationship between RV systolic function and RV after load was demonstrated in patients with pulmonary hypertension . Our findings were compatible with a previously tissue Doppler study which reported the relationship between pulmonary vascular bed and RV function in patients with ASD .…”
Section: Discussionsupporting
confidence: 92%
“…10,37 Negative relationship between RV systolic function and RV after load was demonstrated in patients with pulmonary hypertension. 38,39 Our findings were compatible with a previously tissue Doppler study which reported the relationship between pulmonary vascular bed and RV function in patients with ASD. 40 In our study, the correlation coefficient between regional EF in the inflow compartment and PVR was the highest among the three compartments, indicating RV regional systolic function in the inflow compartment is more sensitive to after load than the other two regions.…”
Section: Discussionsupporting
confidence: 92%
“…Potential reasons proposed for the underestimation of RV volumes on RT3DE include the difficulties with accuracy of endocardial drawings which (due to the sequential nature of the software calculation) meant that even a small initial deviance would result in a much larger difference in the final estimation. A recent study assessed the ability of segmental RV function analysis with RT3DE to predict pulmonary artery hypertension (PAH) with right heart catheterization in a small group patients (n = 24) . The authors concluded that RT3DE identified the RV inflow portion to contribute the most to overall RVEF and it best predicted PAP.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest are the novel advances in three-dimensional echocardiography which offer the prospect of the assessment of right ventricular volume in an accurate way in PAH. This technique offers advantages above MRI, namely that simultaneous measurements [40] can be performed during right heart catheterisation in almost every clinic, which will lower the hurdle to assessing right ventricular function in a proper way in the clinical environment, allowing for large scale studies.…”
Section: Future Perspectivesmentioning
confidence: 99%